6-Mercaptopurine Self-Assembled Monolayers on Gold (001)-Hex: Revealing the Fate of Gold Adatoms - Carro, Pilar (2017)
Thiol molecules adsorbed on gold became a model system for molecular self-assembly on metal substrates long ago. In most cases the strong molecule-gold interaction is able to restructure the substrate, resulting in vacancy islands and steps. Today it is widely accepted that gold adatoms produced by this process form stable thiol-adatom complexes, usually termed "staples" (RS-Auad-SR or RS-Auad-SR-Auad-SR), which are the basic units of the self-assembled monolayers. Here we report on a different scenario for 6-mercaptopurine (6MP), a heterocyclic aromatic thiol, namely its adsorption on the Au(001)-(5 × 20) reconstructed surface. Our results show that 6MP lifts the reconstruction upon adsorption, thus ejecting a large excess of gold adatoms. Surprisingly, 6MP molecules prefer to arrange in highly ordered adatom-free domains in the bridging configuration, while the ejected adatoms form gold islands. Our investigation reveals that the formation of thiol-gold adatom complexes is not always a thermodynamically favored process but rather depends on the nature of the thiol molecule.